The holism of aesthetic knowing in nursing - Archibald, Mandy M. (Nursing philosophy, 2012)
In 1978, Carper identified ‘four fundamental patterns of knowing’ that became largely foundational to subsequent epistemological discourse within the nursing discipline. These patterns of empirical, personal, aesthetic, and ethical knowing were presented as conceptually distinct yet related patterns of knowing. In order to provide an alternative conceptualization of aesthetics in nursing, the main tenants of Carper's discussion of aesthetic knowing will be revisited, and the foundations for her arguments will be examined. Specifically, Dewey's Art as Experience will be examined in relation to the ‘holism’ of nursing, and an alternative position on pragmatic aesthetics in nursing will be offered. A preliminary reintegration of the four patterns of knowing will then be presented as will an example of a potential cultivation of aesthetics in nursing, through an example of Rodin's 19th century sculpture, the Burghers of Calais.